Intimate Partner Violence and Risk Factors Associated with it amongst Married Women in Belagavi: A Cross-sectional Study - K Kruthika; Sulakshana S Baliga; Nilesh N Jadhav (Medsci Publications, 2017)
Background: Intimate partner violence (IPV) has been emerged as an important social problem in India. Considerable number of women experience violence in their lifetime resulting in long and short-term physical and psychological trauma for many. Screening at early stages of violence can prevent many mortality and morbidity among IPV sufferers. Objective: To study the prevalence and potential risk factors of Intimate partner violence among married women in an urban area. Methods: A cross sectional study was conducted from November 2015 to June 2016 amongst 214 married women attending the outpatient department of three urban health centres by interviewing them using WHO multi-country study questionnaire. Results: The Overall prevalence of Intimate partner violence was 39.25% of which 39.2% of women experienced physical violence, 14% of women had experienced Sexual violence and 19.1% of the women had experienced controlling behaviour by their partners.